2002
DOI: 10.1071/rd01120
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inbreeding on testicular sperm concentration in Peromyscus polionotus

Abstract: Inbreeding effects on fitness have most often been quantified via juvenile mortality. However, inbred adults may suffer from inbreeding depression if their fertility or fecundity is compromised as a consequence of inbreeding. Here, the effects of inbreeding on male fertility in oldfield mice, Peromyscus polionotus, were examined. Testicular sperm concentration was assessed in 93 males, 68 of which were paired for breeding. Forty of the 68 paired males failed to produce offspring. Total testicular sperm count, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Previous research in oldfield mice (Peromyscus polionotus) showed the same pattern, with a transient increase in testes size for low levels of f that is eventually reversed at the higher inbreeding levels [32]. However, we failed to detect a negative correlation between proportion of normal sperm and absolute/relative testes size (results not shown) at the f levels considered, so this question deserves further attention.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous research in oldfield mice (Peromyscus polionotus) showed the same pattern, with a transient increase in testes size for low levels of f that is eventually reversed at the higher inbreeding levels [32]. However, we failed to detect a negative correlation between proportion of normal sperm and absolute/relative testes size (results not shown) at the f levels considered, so this question deserves further attention.…”
Section: Discussionsupporting
confidence: 62%
“…Another study in captive populations of Mexican wolf (Canis lupus baileyi) [31] found a similar result, although in this case, the comparison involved pooling subjects from different captive populations (f range, 0-0.6). Regarding sperm production, negative [32] and positive [33] relationships between inbreeding and sperm production have been reported.…”
Section: Introductionmentioning
confidence: 96%
“…number and abnormalities) have often been associated with inbreeding depression (e.g. Wildt et al 1987;Roldan et al 1998;Margulis and Walsh 2002;Gage et al 2006), we also examined sperm number in the inbred and outbred male offspring.…”
Section: Offspring Life History Traitsmentioning
confidence: 99%
“…High levels of inbreeding may be a cause of poor semen quality (Wildt et al, 1982;Margulis and Walsh, 2002;Aurich et al, 2003;van Eldik et al, 2006). Using pedigree data and analyses of sperm quality, Maximini et al (2011) showed that inbreeding depression reduced fertility of Fleckvieh (i.e., dual-purpose Simental) bulls.…”
Section: Introductionmentioning
confidence: 98%